ANALYSIS AND EVALUATION OF FLOOD ROUTING USING MUSKINGUM METHOD - Alhumoud, Jasem (Journal of Applied Engineering Science, 2022)
There are several mathematical procedures that deal with hydrologic flood routing. The Muskingum technique is one of the most common techniques used for flood routing for river reach. From the hydrologic point of view, flood routing in a stream is used to predict the flood discharge, or storage, at any downstream station in a stream channel from a known discharge, or stage, at an upstream station. Hydrologic routing is an approximate technique. However, it provides relatively easy alternative, for solving flood routing problems. It is based on the storage and the continuity equations. In principle hydrologic routing employs historical data on inflow and outflow discharges in the reach under study. The Muskingum method is the particular one to be considered in this paper, describing three procedures, other than the classical trial and error procedure, for solving flood routing.
Keywords: Muskingum method, hydraulic routing, hydrologic routing, K, x